Pemanfaatan Gen-AI dalam perancangan: Kajian respons praktisi kreatif di Indonesia - Wisnu Kusuma Mandala; Achmad Syarief; Elda Franzia (Institut Seni Indonesia Yogyakarta, 2026)
In an increasingly competitive digital era, the Indonesian creative industry faces significant challenges in producing innovative and relevant designs. This research aims to examine the role of visual generative AI in enhancing creativity, efficiency, and the quality of design product, particularly within the creative advertising sector. Utilizing a mixed-methods approach with a sequential exploratory design, this study involves a literature review, design experiments for IziBrizi brand advertisements, and a survey of 23 creative professionals (including designers, art directors, and advertising agency CEOs). The findings indicate that the use of generative AI significantly improves workflow efficiency, design quality, and the potential for consumer emotional engagement. The novelty of this research lies in the application of generative AI within the local Indonesian context, providing profound insights for practitioners to adapt and compete globally. These findings serve not only as a guide for academics and practitioners but also align with the Sustainable Development Goals (SDGs), specifically Quality Education and Industry, Innovation, and Infrastructure.